RANCANG BANGUN DASHBOARD DAN VISUALISASI DATA KICKSTARTER DENGAN PENDEKATAN BUSINESS INTELLIGENCE - Hafidz, Irmasari; Mirfak, Achmad; Azhari, Anisah; Adianto, Aufar Ilham; Fuad, Berry Humaidi; Farabi, M. Ihsan (Department of Information Systems, Institut Teknologi Sepuluh Nopember, 2019)
Kickstarter is one of the most famous worldwide crowdfunding platforms. Pebble smart watch slash wearable technology is one example of successful story on Kickstarter. With current trend on how successful a project can be delivered until its product launch, Kickstarter must analyze its data to asses which projects that is successful and how its revenue progress. With business intelligence approach, Kickstarter could make performance evaluation from three aspects, such as Strategic, Management, and Operational. This will detect which project is failed to reach their goal and how project grow each region. Based on our approach, there are four types of insights, namely descriptive, diagnostic, predictive, and prescriptive insights. This insight could be used as a reference for companies reaching their goals. Although there are some of the biggest and most-pledged projects done in 2015, Kickstarter hit their worst year because they found that many projects could not reach their target. However, respectively in 2016 and 2017 Kickstarter had their percentage of success projects increase slowly although there are many competitors, such as new crowdfunding platform.